Viral lysis as top-down control of bacterial production in tropical waters of Peninsular Malaysia / Stanley Chai Choon Yip - Stanley Chai , Choon Yip (2021)
Viruses are the most abundant biological entities in the biosphere. Viruses infect host cells for replication and survival. Hence, viruses play important roles in the nutrient cycles and genetic transfer. Viral lytic and lysogenic life cycles have different effects to the ecosystem as lytic cycle leads to production of more virus particles and death of host cells whereas lysogenic cycle produces prophage that reproduce along with the host cell. However, the environmental changes such as temperature increment and eutrophication may cause the shift of the lysogenic to lytic life cycle which may affect the host cell community. The changes of viral life cycle and community structure of bacteria and phytoplankton due to environmental change will bring significant consequences onto biogeochemical cycles. The water samples were collected from nearshore (Port Klang and Port Dickson) and offshore waters (Yan and Kuala Rompin) surrounding Peninsular Malaysia. Bacterial production, virus production and protist grazing at each sampling sites were measured. Microcosm experiment were carried out to determine the relationship of seawater warming and eutrophication with viral dynamics. Mitomycin C was used to induce viral lytic life cycle. Observations revealed site-dependent differences in dissolved inorganic nutrient concentration, TSS (43.3 – 106.7 mg L-1), dissolved oxygen (148 – 265 μM), Chl a (0.21 – 3.54 μg L–1) and bacterial abundance (4.09 × 105 – 9.41 × 105 cells mL–1). However viral abundance (measured as virus-like particles or VLP) (1.04 × 106 – 2.39 × 106 VLP mL–1) and virus production rates (0.59 × 105 – 4.55 × 105 VLP mL–1 h–1) were not coupled to neither bacterial abundance nor production (0.85 × 104 – 6.42 × 104 cells mL–1 h–1). The uncoupling was probably due to the bacterial replete state as suggested by the low virus to bacteria ratio (1.8 – 4.3). Ex situ experiments were carried out to investigate the effects of seawater warming (25 – 37°C) and eutrophication (0.1 – 1.0× marine broth concentration) on viral dynamics. Both seawater warming and eutrophication were able to induce lysogen to switch from lysogenic to lytic cycle as the result showed increased virus production (R2 > 0.537) and decreased lysogeny (R2 > 0.896). From this study, eutrophication was a more important driver for virus production. Therefore, with the increasing eutrophication at the coastal waters, the role of viruses in the marine microbial food web will gain importance as virus production increases. Enhanced virus production will drive the habitat towards heterotrophy as increased viral lysis will promote organic matter supplies for the bacterial growth, and will further affect biogeochemical cycling.